2014
DOI: 10.1186/1479-5876-12-196
|View full text |Cite
|
Sign up to set email alerts
|

Mir-208 promotes cell proliferation by repressing SOX6 expression in human esophageal squamous cell carcinoma

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) is the major histological type of esophageal cancer in developing countries. The prognosis and survival rate of ESCC are very poor. Recently, microRNAs (miRNAs) have emerged as important regulators of cancer cell biological processes. To better understanding the molecular mechanisms by which they regulate the behavior of cancer cells is needed.MethodsThe expression of miR-208 was examined in ESCC cell lines and tumor tissues by real-time PCR. Proliferation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 30 publications
5
63
0
2
Order By: Relevance
“…Cyclin D1 was inversely associated with Axin level in the lung cancer cell line (32), and β-catenin regulated the expression of cyclin D1 in colon carcinoma cells (33). Cyclin D1 expression and phosphorylation of Rb were also increased by another miRNA, miR-208, which promoted cell proliferation when ectopically expressed in esophageal squamous cell carcinoma lines (22). Thus, the increased expression of cyclin D1 and phosphorylation of Rb by miR374a provided a further mechanism for the tumor-promotive effect of miR-374a.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Cyclin D1 was inversely associated with Axin level in the lung cancer cell line (32), and β-catenin regulated the expression of cyclin D1 in colon carcinoma cells (33). Cyclin D1 expression and phosphorylation of Rb were also increased by another miRNA, miR-208, which promoted cell proliferation when ectopically expressed in esophageal squamous cell carcinoma lines (22). Thus, the increased expression of cyclin D1 and phosphorylation of Rb by miR374a provided a further mechanism for the tumor-promotive effect of miR-374a.…”
Section: Discussionmentioning
confidence: 98%
“…The number of colonies was counted at the 5th day after seeding. The trypsinized cells were also seeded for an anchorage-independent growth ability assay as previously described (22). One thousand cells were suspended in 2 ml complete medium plus 0.33% agar.…”
Section: Stable Transfection Of Mir-374a In Eca109 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal expression of miRNAs has been detected in a number of tumors and contributed to tumor initiation and progression. Specifically, miR-208 has been rarely studied in cancers [33,34], whereas a role of miR-208 in PC has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (13) reported that hsa-miR208a induced epithelial cells converted to mesenchymal cells, promoted the pancreatic cancer cell metastasis and invasion, the overexpression was concerned with the activation of AKT/GSK-3β/snail signaling pathway. Li et al (12) have reported that hsa-miR-208a promoted the proliferation of human esophageal squamous cell carcinoma by inhibiting the expression of SOX6. Chen et al (1) have reported that hsamiR-1207-5p inhibited the growth of gastric cancer cells by acting on telomerase reverse transcriptase.…”
Section: █ Discussionmentioning
confidence: 99%